Histidine-rich stabilized polyplexes for cMet-directed tumor-targeted gene transfer1. Issue 12 (28th March 2015) - Kos, Petra; Lächelt, Ulrich; Herrmann, Annika; Mickler, Frauke Martina; Döblinger, Markus; He, Dongsheng; Krhač Levačić, Ana; Morys, Stephan; Bräuchle, Christoph; Wagner, Ernst
<x xml:space="preserve">Abstract</x> The first report of tumor-targeted non-viral gene delivery exploiting c-Met as the cell surface receptor by using improved stabilized and histidines-enriched oligo(ethanamino)amides.